2022
DOI: 10.3389/fcell.2022.995508
|View full text |Cite
|
Sign up to set email alerts
|

Native valve, prosthetic valve, and cardiac device-related infective endocarditis: A review and update on current innovative diagnostic and therapeutic strategies

Abstract: Infective endocarditis (IE) is a life-threatening microbial infection of native and prosthetic heart valves, endocardial surface, and/or indwelling cardiac device. Prevalence of IE is increasing and mortality has not significantly improved despite technological advances. This review provides an updated overview using recent literature on the clinical presentation, diagnosis, imaging, causative pathogens, treatment, and outcomes in native valve, prosthetic valve, and cardiac device-related IE. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 253 publications
(459 reference statements)
0
11
0
Order By: Relevance
“…Subacute infection has insidious onset and presents with nonspecific symptoms, such as fever, chills, sweats, or shortness of breath. Other clinical signs include skin lesions such as Osler’s nodes, Janeway lesions, splinter hemorrhages, petechiae, and clubbing [ 8 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Subacute infection has insidious onset and presents with nonspecific symptoms, such as fever, chills, sweats, or shortness of breath. Other clinical signs include skin lesions such as Osler’s nodes, Janeway lesions, splinter hemorrhages, petechiae, and clubbing [ 8 ].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…(5%). 10 Despite the development of diagnostic tools, there are still up to 50% in-hospital mortality. 43 No significant improvement compared to the last decades.…”
Section: Non-culture-based Diagnostic Tools For Culture-negative Endo...mentioning
confidence: 99%
“…This increase is mainly due to age-related degenerative valvular disease and the increased need for cardiac devices and invasive procedures including hemodialysis for end-stage renal failure. 10 , 11 In a retrospective cohort study, with a total of 405 patients with definite infective endocarditis, showed patients older than 65 years old had more predisposing factors including previous cardiac surgery history and degenerative heart disease compared with younger patients. 12 In the past 20 years, with the development of techniques, the etiology of infective endocarditis has changed due to an increase in cardiac device implantation and prosthetic valve proportion.…”
Section: Introductionmentioning
confidence: 99%
“…The vegetations correspond to a septic thrombus, whose growth is promoted by the activation of hemostasis by cytokines. Microorganisms that have colonized the vegetations are difficult to access by antibiotics and immune defenses [9].…”
Section: Of 16mentioning
confidence: 99%